Nickel in terrestrial biota: Comprehensive review on contamination, toxicity, tolerance and its remediation approaches - Kumar, Amit; Jigyasu, Dharmendra K.; Kumar, Amit; Subrahmanyam, Gangavarapu; Mondal, Raju; Shabnam, Aftab A.; Cabral-Pinto, M.M.S.; Malyan, Sandeep K.; Chaturvedi, Ashish K.; Gupta, Dipak Kumar; Fagodiya, Ram Kishor; Khan, Shakeel A.; et al. (Chemosphere (Oxford), 2021)
Nickel (Ni) has been a subject of interest for environmental, physiological, biological scientists due to its dual effect (toxicity and essentiality) in terrestrial biota. In general, the safer limit of Ni is 1.5 μg g−1 in plants and 75–150 μg g−1 in soil. Litreature review indicates that Ni concentrations have been estimated up to 26 g kg−1 in terrestrial, and 0.2 mg L−1 in aquatic resources. In case of vegetables and fruits, mean Ni content has been reported in the range of 0.08–0.26 and 0.03–0.16 mg kg−1. Considering, Ni toxicity and its potential health hazards, there is an urgent need to find out the suitable remedial approaches. Plant vascular (>80%) and cortical (<20%) tissues are the major sequestration site (cation exchange) of absorbed Ni. Deciphering molecular mechanisms in transgenic plants have immense potential for enhancing Ni phytoremediation and microbial remediation efficiency. Further, it has been suggested that integrated bioremediation approaches have a potential futuristic path for Ni decontamination in natural resources. This systematic review provides insight on Ni effects on terrestrial biota including human and further explores its transportation, bioaccumulation through food chain contamination, human health hazards, and possible Ni remediation approaches. •Nickel can be essential or toxic in terrestrial ecosystem based on its concentration.•Low Ni in plant embryonic tissues ensures high reproductive success.•PGPBs required filed optimization for successful Ni bioremediation.•Short duration low-frequency microwave irradiation enhances seed germination.•Microbes use Ni efflux systems, for regulating Ni toxicity.